Developing dialogic teaching: genesis, process, trial. Issue 5 (20th October 2018) - Alexander, Robin
ABSTRACT: This paper considers the development and randomised control trial (RCT) of a dialogic teaching intervention designed to maximise the power of classroom talk to enhance students' engagement and learning. Building on the author's earlier work, the intervention's pedagogical strand instantiates dialogic teaching not as a single, circumscribed 'method' but as an interlocking set of permissive repertoires through which, steered by principles of procedure, teachers energise their own and their students' talk. The repertoires are directed both to teaching's improvement and to its larger epistemological, cultural and civic purposes. Its professional strand entailed teacher induction and training followed by a cyclic programme of planning, target-setting and review using mentoring and video/audio analysis. Supported by the UK Education Endowment Foundation it was piloted in London and trialled in three other UK cities with combined intervention/control cohorts of nearly 5000 year 5 (4th grade) students and 208 teachers. The independent evaluation calculated that after 20 weeks students in the intervention group were two months ahead of their control group peers in English, mathematics and science tests; while coded video data showed that the changes in both teacher and student talk were striking and in the direction intended. The RCT methodology affords limited explanatory purchase but insights are available from other studies. These, together with contingent questions and future possibilities, are discussed in the paper's conclusion.